Increased Percentage of Microvessels but Decreased Density of Large Vessels in Papillary Carcinomas as Compared to Hot and Cold Thyroid Nodules - (:unkn) unknown (JOHANN AMBROSIUS BARTH VERLAG MEDIZINVERLAGE HEIDELBERG GMBH, 2009)
Objective: For thyroid tumors increased as well as decreased vessel densities have been reported. Because of different morphometric methods and specificities of previously used antibodies for small and large vessels our objective was to investigate and compare the density of large vessels and microvessels by different morphometric methods and antibodies in hot nodules(HN), cold nodules (CN), papillary carcinoma (PC) and Graves' disease (GD) to try to clarify some of these discrepancies. Design: Tissue sections from 29 HN, 22 CN, 19 PC and 8 GD thyroids were stained with the antibodies for CD34 and alpha-SMA. A computerized image analysis was used to calculate the mean area of endothelium (mEA) and the mean endothelium to tumor epithelial nucleus area ratio (mE/N) in four hot spots and ten systematically selected fields. Main outcome: We found a consistent increase of the CD34 stained percentage of microvessels in PC as compared to HN and CN determined by the hot spot analysis and systematic field analysis. This increased microvessel density in PC is of a similar magnitude as in GD, which is characterised by a prominent increase of vascularisation during its active disease stage. Our SMA staining results reveal a kind of mirror image of the CD34 staining results with higher vessel counts in the normal surrounding tissues as compared to HN, CN and PC. Conclusions: The specific immunohistologic detection of microvessels with the CD34 antibody combined with their specific evaluation is able to clearly differentiate PCs from normal tissue, HN and CN.
Keywords: multiple endocrine neoplasia; cancer; thyroid; autoimmunity; Graves' disease; TUMOR ANGIOGENESIS; CERVICAL-CANCER; QUANTIFICATION; VASCULARITY; INDICATOR; ADENOMAS; MARKERS; LESIONS